Cross-cultural Design and Healthcare Waiting Rooms for Indigenous People in Regional Australia. Issue 1 (January 2022) - O'Rourke, Timothy; Nash, Daphne; Haynes, Michele; Burgess, Meredith; Memmott, Paul
The theory of supportive design influences healthcare facility design but is under-researched for different cultural groups. This mixed-methods study compared two Indigenous sample populations in Australia to examine the effect of the physical environment in public hospitals and clinics on Indigenous people's perceptions and experiences of waiting for care. Quantitative survey data ( n  = 602) measured perceptions of relevant design attributes using paired images in a screen-based survey. Semi-structured interviews ( n  = 55) identified concerns about the physical healthcare environment including waiting rooms. Ceiling heights, seating arrangements and views to the outside were significant showing commonalities between perceptions of the two populations. The interviews revealed that cultural and social constructs, including privacy, fear, shame, and racism, were significant and that people's perceptions were influenced by colonization and independent of location. Our study highlights the importance of a cross-cultural approach to supportive design interventions for spatial and symbolic treatments of waiting areas.